Who is likely to benefit from public and private sector investments in farmer-led irrigation development? Evidence from Ethiopia - Kafle, Kashi; Omotilewa, O.; Leh, Mansoor; Schmitter, Petra S. (Informa UK Limited, 2022)
In recent years, farmer-led irrigation development has gained the interest of development partners and governments in the Global South following its success in enhancing agricultural production and livelihoods in South Asia. However, little is known about the socio-economic situation of farmers who receive public support for its expansion. Considering its rapid expansion in sub-Saharan Africa, we take the case of Ethiopia and explore the relationship between irrigation suitability and farmers’ socio-economic status. We find that high-value crop producers and wealthier farmers are most likely to make private investments and also benefit from public support in farmer-led irrigation expansion if investments are directed to land areas highly suitable for irrigation. Cultivation of high-value crops (fruit, vegetables) was common in areas more suitable for irrigation but staple crop cultivation (cereals, legumes) was negatively associated with irrigation suitability. Wealth status (consumption expenditure, asset index, and land size) was also positively correlated with irrigation suitability. A 10 per cent increase in groundwater irrigation suitability score was associated with a 2 per cent increase in per-capita consumption expenditure. Results imply that policies aiming to facilitate farmer-led irrigation development should combine biophysical information on land and water suitability for irrigation with household socio-economic characteristics and existing agricultural systems.